Comparison of marine and river water humic substances in a Patagonian environment (Argentina) - Scapini, Maria del Carmen (2010)
Structural aspects of humic substances (HSs) in marine waters of Engaño Bay (Atlantic Ocean) and water from the Chubut River (Patagonia, Argentina) were compared. The HSs were isolated, purified, and analyzed using a multiple-method approach for structural characterization: elemental analysis, nuclear magnetic resonance (13C and 1H NMR), infrared spectroscopy (FTIR), UV-visible absorption and fluorescence. Similarities between the marine and freshwater components were evaluated on the basis of N and O contents, H/C and C/N atomic ratios, infrared bands from nitrogen-containing and carboxylic groups, percentage of functional groups obtained from NMR spectra, spectral slope coefficient of absorption spectra, absorbance ratios at 250 and 365 nm (E2/E3), aromaticity, excitation–emission matrices and fluorescence quantum yield. Both the Engaño Bay and Chubut River waters have HSs that are mainly composed of fulvic acids (FAs); although they are very similar, they may be distinguished from one another. Similarities include the predominance of aliphatic carbon content (low aromatic content); however, the water bodies differed in their content of proteins and carboxylic acids. The Engaño Bay FAs have mainly an aquatic origin; although the Chubut River FAs suggest a similar aquagenic origin, there is also evidence of contributions from pedogenic FAs.